Neuropediatrics postgraduate students’ learning process through hidden curriculum at Universidad Nacional de Colombia - Angélica María Uscátegui-Daccarett; María Luz Sáenz-Lozada (Revista de la Facultad de Medicina, 2016)
Based on the importance of a comprehensive professional training, this research aims at observing and describing the learning process achieved through the hidden curriculum of students enrolled in the Neuropediatrics Specialization Program at Universidad Nacional de Colombia in 2012 y 2013. A qualitative study to explore students’ training, transmission of attitudes, values and ethical aspects was performed through the implementation of a semi-structured interview and a focal group. For this group of students, learning through the hidden curriculum is real and educational, allows having a better approach to patients and acquiring appropriate tools for a successful job performance. Nevertheless, it is still insufficient to address ethical dilemmas such as delivery of bad news and patients’ deaths. Thus, complementing this type of learning with explicit training on bioethics is required.